A promising load carrier grafting material; Sintered enamel hydroxyapatite bodies - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
The excellent bone bonding and osteoconductive capacities of bulk hydroxyapatite (HA) are well known and have been extensively researched. Dental enamel has a very high load resistance capability which can be attributed to its fluoride content. However the osseeointegration and load carrying abilities of dental enamel has not been thoroughly studied in literature. In this study, the compacts made of enamel HA were sintered at 1000, 1100, 1200 and 1300degreesC. The density, microhardness and compression strength tests have been performed, in order to find out the optimum sintering temperature. As a result, that all findings are supportive to the available literature, have been identified. The in vivo tests are still in progress.
Keywords: hydroxyapatite; enamel; florine; sintering; mechanical properties